Brain-targeted delivery of PEGylated nano-bacitracin A against Penicillin-sensitive and -resistant Pneumococcal meningitis: formulated with RVG29 and Pluronic® P85 unimers. (1st January 2018) - Hong, Wei; Zhang, Zehui; Liu, Lipeng; Zhao, Yining; Zhang, Dexian; Liu, Mingchun
Abstract: Pneumococcal meningitis (PM), caused by Streptococcus pneumonia, remains a high-burden disease in developing countries. Antibiotic therapy has been limited due to the inefficiency of drug transport across the blood-brain barrier (BBB) and the emergence of drug-resistant strains. In our preliminary study, PEGylated nano-self-assemblies of bacitracin A (PEGylated Nano-BA12K ) demonstrated a strong antibacterial potency against S. pneumonia . In this study, the potential application of this micelle for the treatment of both Penicillin-sensitive and -resistant PM was studied. To address BBB-targeting and -crossing issues, PEGylated Nano-BA12K was formulated with a specific brain-targeting peptide (rabies virus glycopeptide-29, RVG29 ) and a P-glycoprotein inhibitor (Pluronic ® P85 unimers) to construct a mixed micellar system (RVG29 -Nano-BAP85 ). RVG29 -Nano-BAP85 demonstrated a strong antibacterial potency against 13 clinical isolates of S. pneumonia, even higher than that of Penicillin G, a conventional anti-PM agent. RVG29 -Nano-BAP85 had more cellular uptake in brain capillary endothelial cells (BCECs) and higher BBB-crossing efficiency than single formulated Nano-BAs as shown in an in vitro BBB model. The enhanced BBB-permeability was attributed to the synergetic effect of RVG29 and P85 unimers through receptor-mediated transcytosis, exhaustion of ATP, and reduction in membrane microviscosity. In vivo results further demonstrated that RVG29 -Nano-BAP85 was able to accumulate in brain parenchyma as confirmed by in vivo optical imaging. In addition, RVG29 -Nano-BAP85 exhibited high therapeutic efficiencies in both Penicillin-sensitive and -resistant PM mouse models with negligible systemic toxicity. Collectively, RVG29 -Nano-BAP85 could effectively overcome BBB barriers and suppressed the growth of both drug-sensitive and -resistant S. pneumonia in the brain tissues, which demonstrated its potential for the treatment of PM.